An introduction to satellite communications - Dalgleish, D. I. (Don I.) (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1989)
The book describes the development of communications satellite services and explains how satellites and earth stations have evolved to meet changing requirements. It deals in a simple but practical way with the physics and geometry of the geostationary orbit, and the construction and operation of satellites and launch vehicles. It gives a thorough analysis of the essential factors governing the quality of speech, data and television signals received via satellite. Particular attention is paid to growth areas in satellite communications, including analogue television transmission, digital methods of transmission of speech and data, the use of satellites for maritime, aeronautical and land-mobile communications and VSATs (very-small aperture terminals).